Effect of the Genotypic Variation of an Aphid Host on the Endosymbiont Associations in Natural Host Populations - Francisca Zepeda-Paulo; Blas Lavandero (Insects, 2021)
Understanding the role of facultative endosymbionts on the host’s ecology has been the main aim of the research in symbiont–host systems. However, current research on host–endosymbiont dynamics has failed to examine the genetic background of the hosts and its effect on host–endosymbiont associations in real populations. We have addressed the seasonal dynamic of facultative endosymbiont infections among different host clones of the grain aphid Sitobion avenae, on two cereal crops (wheat and oat) and whether their presence affects the total hymenopteran parasitism of aphid hosts at the field level. We present evidence of rapid seasonal shifts in the endosymbiont frequency, suggesting a positive selection of endosymbionts at the host-level (aphids) through an agricultural growing season, by two mechanisms; (1) an increase of aphid infections with endosymbionts over time, and (2) the seasonal replacement of host clones within natural populations by increasing the prevalence of aphid clones closely associated to endosymbionts. Our results highlight how genotypic variation of hosts can affect the endosymbiont prevalence in the field, being an important factor for understanding the magnitude and direction of the adaptive and/or maladaptive responses of hosts to the environment.